Sarcoidosis and Systemic Sclerosis: Strange Bedfellows - Micah Yu; Vaneet K. Sandhu; Sheila D. Lezcano; Kanwaljeet Maken; Shannon Kirk; Karina D. Torralba (Case Reports in Rheumatology)
Coexistence of systemic sclerosis and sarcoidosis is rare. Both have predominant lung manifestations, each with distinctive features on computed tomography (CT) of the chest. We present herein a 52-year-old male with limited systemic sclerosis manifested primarily by sclerodactyly and subsequently by shortness of breath. A series of CT scans of the chest were reviewed. Initial CT chest one year prior to sclerodactyly onset revealed bilateral hilar and right paratracheal, prevascular, and subcarinal adenopathy. Five-year follow-up demonstrated thin-walled cysts, mediastinal lymphadenopathy, and nonspecific nodules. Due to progression of dyspnea, follow-up CT chest after one year again demonstrated multiple cysts with peripheral nodularity and subpleural nodules, but no longer with hilar or mediastinal adenopathy. Diagnostic open lung biopsy was significant for noncaseating granulomas suggestive of sarcoidosis. This is the first known case of a patient with systemic sclerosis diagnosed with sarcoidosis through lung biopsy without radiographic evidence of hilar or mediastinal lymphadenopathy at the time of biopsy. A review of cases of concomitant sarcoidosis and systemic sclerosis is discussed, including the pathophysiology of each disease with shared pathways leading to the development of both conditions in one patient.